2018
DOI: 10.1002/aenm.201801430
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Degradation in Si‐Based All‐Solid‐State Li‐Ion Microbatteries

Abstract: Like all rechargeable battery systems, conventional Li-ion batteries (LIB) inevitably suffer from capacity losses during operation. This also holds for all-solid-state LIB. In this contribution an in operando Neutron Depth Profiling (NDP) method is developed to investigate the degradation mechanism of all-solid-state, thin film Si-Li 3 PO 4 -LiCoO 2 batteries. Important aspects of the long-term degradation mechanisms are elucidated. It is found that the capacity losses in these thin film batteries are mainly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 58 publications
0
83
0
Order By: Relevance
“…On the other hand, directly forming bonds, introducing intermediate layers, and direct growth of electrodes on current collectors are useful strategies for producing strongly coupled interfaces between microelectrodes and current collectors. As demonstrated in Si–Li 3 PO 4 –LiCoO 2 MBs, the formation of lithium immobilization layer at the interface between electrode and solid electrolyte has a remarkable influence on the cycling performance . Therefore, more studies should be devoted to the interfacial engineering, including the composition, modification, evolution, and dynamics of the interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, directly forming bonds, introducing intermediate layers, and direct growth of electrodes on current collectors are useful strategies for producing strongly coupled interfaces between microelectrodes and current collectors. As demonstrated in Si–Li 3 PO 4 –LiCoO 2 MBs, the formation of lithium immobilization layer at the interface between electrode and solid electrolyte has a remarkable influence on the cycling performance . Therefore, more studies should be devoted to the interfacial engineering, including the composition, modification, evolution, and dynamics of the interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The NDP technique was first reported by J. Ziegler, G. W. Cole and J. E. E. Baglin in 1972 as a non-destructive tool to study 10 B impurities inside silicon substrates (1). Around the same time and independently similar experimental approach was used by J. P. Biersack and D. Fink (2).…”
Section: Introductionmentioning
confidence: 99%
“…Only in this case, an Li profile through the entire battery cell can be derived with high resolution by analysis of α-particle signal. Examples of NDP being applied to operando study solid-state thin-film LIB can be found in (9,10). The moderate neutron flux and single charged particle detector available at the NDP facility (9, 10) made 10 min measurement time for a single NDP spectrum possible.…”
Section: Introductionmentioning
confidence: 99%
“…42 Besides this, the ability to measure the 6 Li isotope independent of oxidation state allows for the simultaneous detection of lithium in both electrode and electrolyte, which makes NDP a unique diagnostic tool capable of unraveling the space- and time-dependent lithium density resulting from the complex electrochemical processes taking place across battery electrodes. 37,44,45…”
Section: Introductionmentioning
confidence: 99%